MEKANISME PERLINDUNGAN ANAK MENURUT PERDATA ISLAM - Isman Nuddin Ritonga; Faisar Ananda (Kampus Akademik Publiser, 2026)
Child protection within the framework of Islamic civil law constitutes an integral part of family law aimed at ensuring the fulfillment of children's rights comprehensively, including aspects of custody (hadhanah), financial support, education, and protection from discrimination and violence. This study examines the mechanisms of child protection in Islamic civil law and their relevance within the Indonesian legal context using a normative juridical method supported by recent scholarly literature. The findings indicate that child protection mechanisms are primarily implemented through custody arrangements based on the best interests of the child, the obligation of parents to provide financial support, and the safeguarding of civil rights such as inheritance and identity. In cases of divorce, judicial institutions play a crucial role in supervising and enforcing children's rights, including restricting parental access when it harms the child's well-being. Additionally, issues related to adopted children highlight the need for harmonization between Islamic law and national civil law to ensure legal certainty. However, challenges remain in implementation, including low legal awareness, non-compliance with financial obligations, and weak enforcement of court decisions. Therefore, strengthening regulations, enhancing judicial oversight, and integrating Islamic legal principles with positive law are necessary to ensure effective and just child protection, with the principle of the best interests of the child as the primary foundation.